2019
DOI: 10.3390/metabo9110248
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 1H NMR Metabolomics Reveal Distinct Metabolic Adaptations in Human Macrophages Following Differential Activation

Abstract: Macrophages (MΦs) are phagocytic immune cells that are found in nearly all human tissues, where they modulate innate and adaptive immune responses, thereby maintaining cellular homeostasis. MΦs display a spectrum of functional phenotypes as a result of microenvironmental and stress-induced stimuli. Evidence has emerged demonstrating that metabolism is not only crucial for the generation of energy and biomolecular precursors, but also contributes to the function and plasticity of MΦs. Here, 1D 1H NMR-based meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 81 publications
3
40
1
Order By: Relevance
“…In addition, our data indicated that BCM-exposed MΦs exhibit significantly decreased levels of intracellular lactate, relative to PCM-exposed MΦs ( Figure 3 ; Table 1 ). This finding differs from what was previously demonstrated [ 39 ], where a significant increase in both intra- and extracellular lactate was observed in MΦs activated with a combination of lipopolysaccharide (LPS) and interferon-γ relative to resting MΦs. However, MΦs in our current study were only stimulated with bacterial-conditioned media for 1 h prior to metabolite extraction, whereas MΦs in our prior study were activated with purified recombinant human cytokines over a period of 72 h, which may account for this difference.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, our data indicated that BCM-exposed MΦs exhibit significantly decreased levels of intracellular lactate, relative to PCM-exposed MΦs ( Figure 3 ; Table 1 ). This finding differs from what was previously demonstrated [ 39 ], where a significant increase in both intra- and extracellular lactate was observed in MΦs activated with a combination of lipopolysaccharide (LPS) and interferon-γ relative to resting MΦs. However, MΦs in our current study were only stimulated with bacterial-conditioned media for 1 h prior to metabolite extraction, whereas MΦs in our prior study were activated with purified recombinant human cytokines over a period of 72 h, which may account for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Cheng et al demonstrated that leukocytes isolated from patients with sepsis exhibit a shift to aerobic glycolysis, which dissipates following patient recovery [ 77 ]. Our findings provide further evidence that pro-inflammatory stimulation of MΦs induces Warburg-like metabolic traits, as previously reported in M1 MΦs [ 39 , 57 , 78 ]. Accordingly, we postulate that PCM- and BCM-exposed MΦs upregulate glycolysis, a well-known and established metabolic marker of M1 MΦ activation, relative to control MΦs in order to promote M1-like MΦ effector functions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Altered mitochondrial function, in which FAO and OXPHOS are inhibited and the TCA cycle is fragmented to support the use of citrate and aconitate for fatty acid and itaconate production respectively, are core metabolic features of inflammatory macrophage activation 3,6,7,[29][30][31] . These events, alongside increased FA uptake and increased DGAT expression, create an environment in which TG synthesis is promoted.…”
Section: Discussionmentioning
confidence: 99%